The effect of rapeseed stand density on the formation of generative organs - P. Kuchtová; J. Vašák (Plant, Soil and Environment, 2004)
This experiment was carried out for the study of differences in dynamics of formation and reduction of generative organs from the beginning of the flowering to the harvest, under different stand density of the winter rapeseed. The evaluation of the results of the study of stand density, confirms that from the technological point of view it is appropriate to choose a thinner population of rapeseed. Starting with the stand density of 60 plants/m2 we do not observe significant differences in plants during the generative stage, neither in the number of branches nor in the number of created generative organs. At this density (60 plants/m2) a significant reduction of generative organs takes place, especially on the secondary branches. Differences in the number of fertile branches are visible in case of more dense populations only in the harvest. From the point of view of the yield it is more advantageous to support the creation of generative organs on primary racemes by agricultural interventions.